2007
DOI: 10.1190/1.2737104
|View full text |Cite
|
Sign up to set email alerts
|

Inverting for reservoir pressure change using time-lapse time strain: Application to Genesis Field, Gulf of Mexico

Abstract: There are increasing numbers of published examples from around the world in which significant 4D time shifts have been observed in the overburden above producing reservoirs.Indeed, this topic prompted the TLE special section "Rocks under strain" in December 2005. The significance of these 4D observations is that, if we wish to fully understand the 4D signature of compacting reservoirs, we can no longer think of the reservoir in isolation. The seismic response outside the reservoir changes because the nonreserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…1988, Dussealt et al 1993, Bruno and Bilak 1994, Castillo et al 1997, Massonnet et al 1997, Fielding et al 1998, Mossop and Segall 1999, Vasco et al 2000a, Stancliffe and van der Kooij 2001, Schmidt and Burgmann 2003, Vasco and Ferretti 2005 or by timelapse seismic monitoring (Guilbot and Smith 2002, Landro and Stammeijer 2004, Tura et al 2005, Hall 2006, Roste et al 2006, Rickett et al 2007, Staples et al 2007 to constrain volume and fluid pressure changes within a reservoir. Our analysis assumes that a set of deformation measurements have been gathered.…”
Section: Estimating Volume and Pressure Changes Within The Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…1988, Dussealt et al 1993, Bruno and Bilak 1994, Castillo et al 1997, Massonnet et al 1997, Fielding et al 1998, Mossop and Segall 1999, Vasco et al 2000a, Stancliffe and van der Kooij 2001, Schmidt and Burgmann 2003, Vasco and Ferretti 2005 or by timelapse seismic monitoring (Guilbot and Smith 2002, Landro and Stammeijer 2004, Tura et al 2005, Hall 2006, Roste et al 2006, Rickett et al 2007, Staples et al 2007 to constrain volume and fluid pressure changes within a reservoir. Our analysis assumes that a set of deformation measurements have been gathered.…”
Section: Estimating Volume and Pressure Changes Within The Reservoirmentioning
confidence: 99%
“…These studies utilized geodetic data, such as leveling measurements, in order to quantify surface deformation related to fluid production or injection. Currently, time-lapse seismic surveys are providing additional deformation measurements, distributed throughout the overburden (Guilbot and Smith 2002, Landro and Stammeijer 2004, Tura et al 2005, Hatchell and Bourne 2005, Barkved and Kristiansen 2005, Hall 2006, Roste et al 2006, Rickett et al 2007, Staples et al 2007). Recently, the observed deformation has been used to better understand fluid flow and the heterogeneity of flow properties within the reservoir (Vasco et al 2000a, Vasco et al 2001, Du et al 2005, Vasco and Ferretti 2005, Hodgson et al 2007, Vasco et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies highlight the role of pressure changes and associated deformation in observed time-lapse seismic anomalies below, within, and above a producing reservoir (Guilbot & Smith 2002;Landro & Stammeijer 2004;Hatchell & Bourne 2005;Tura et al 2005;Hawkins et al 2007;Hodgson et al 2007;Rickett et al 2007;Roste et al 2007;Schutjens et al 2007;Staples et al 2007). These studies document both changes in layer position and thickness as well as seismic velocity changes due to stress variations.…”
Section: Introductionmentioning
confidence: 97%
“…An example of using time strain for estimation of reservoir pressure changes is shown by Hodgson et al (2007). On the other hand, methods related to seismic interferometry (Snieder et al, 2009;Wapenaar et al, 2011;Galetti and Curtis, 2012) can be used to virtually move surface sources below a complex overburden and therefore enable time-lapse monitoring of reservoir without any velocities of the overburden (Bakulin and Calvert, 2006).…”
Section: Introductionmentioning
confidence: 99%